Intranasal Steroid Use for Otitis Media with Effusion: Ongoing Opportunities for Quality Improvement. (August 2017) - Wang, David E.; Lam, Derek J.; Bellmunt, Angela M.; Rosenfeld, Richard M.; Ikeda, Allison K.; Shin, Jennifer J.
Objectives: Our objectives were (1) to assess patterns of intranasal steroid administration when otitis media with effusion (OME) has been diagnosed in children, (2) to investigate whether usage varies according to visit setting, and (3) to determine if practice gaps are such that quality improvement could be tracked. Study Design: Cross-sectional analysis of an administrative database. Subjects and Methods: National Ambulatory and Hospital Ambulatory Medical Care Surveys, 2005 to 2012; univariate, multivariate, and stratified analyses of intranasal steroid usage were performed. The primary outcome was intranasal steroid administration, and the primary predictor was a diagnosis of OME. The impact of location of service was also analyzed. Results: Data representing 1, 943, 177, 903 visits demonstrated that intranasal steroids were administered in 10.0% of visits in which OME was diagnosed, in comparison to 3.5% of visits in which OME was not diagnosed (univariate odds ratio, 3.07; 95% confidence interval [CI], 1.85-5.08; P < .001). After adjusting for age, sex, race/ethnicity, and other confounding conditions, multivariate analysis demonstrated that OME remained associated with an increase in intranasal steroid usage (odds ratio, 3.58; 95% CI, 1.60-8.01; P = .002). This practice pattern was more prevalent in the ambulatory office setting (risk difference 6.6%, P < .001) and less seen in a hospital-based office or emergency department. Conclusion: Despite randomized controlled trials showing a lack of efficacy for isolated OME, nasal steroids continue to be used in treating children with OME in the United States. Related quality improvement opportunities to prevent usage of an ineffective treatment exist.